PENGARUH PENGERINGAN JAGUNG DENGAN METODE MIXED ADSORPTION DRYING MENGGUNAKAN ZEOLITE PADA UNGGUN TERFLUIDISASI TERHADAP KANDUNGAN LEMAK DAN PROTEIN - JD Ryan Christy S; Muhammad Ulil Absori; Luqman Buchori (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Corn (Zea mays L.) is one of the important world food crops, other than wheat and rice. Becausecorn is an important role as a source of food and medicine, the post-harvest handling is veryimportant because it determines the quality of the corn for the next use. Drying process byadsorption is an option to replace conventional corn drying systems. In our study, the zeolite asadsorbent was mixed with corn in campfire the fluidized with air at 30-50oC. The air willevaporate water from the corn, and at the same time, the zeolite will absorb the water from the air,so the humidity will be maintained low. Thus heat consumption can be lowered and drying willbecome faster. Required materials in this study are corn and zeolite. Research conducted usingfixed variable sampling time (15 minutes). Incoming air temperature(room temp, 30oC, 40oC, 50oC)and ratio between corn and zeolitedrying the corn, characterization must do first. The dried corn tested the water, protein, fatcontains and the colors. The results from this research show the best variable is variable with ratiobetween corn and zeolite (1:0, 1:3, 1:1, 3:1) are used as changing variables. Beforeappropriate with SNI standard for dried food ( 14 % ) is variable using incoming air temperature40oC and 50oC with ratio between corn and zeolite 1 : 3 and using incoming air temperature 50oC. The suitable variable andappropriate with SNI standard for dried food ( 14 % ) is variable using incoming air temperature 40oC and 50oC with ratio between corn and zeolite 1 : 3.